2010
DOI: 10.1590/s0100-40422010000600015
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of biflavones in leaves of Caesalpinia pyramidalis specimens

Abstract: Recebido em 17/9/09; aceito em 2/2/10; publicado na web em 18/6/10The chloroform partition of methanol extract of leaves of Caesalpinia pyramidalis was submitted to different chromatographic procedures which afforded besides agathisflavone and taxifolin, the minor biflavones loniflavone, amentoflavone, 5'-hydroxyamentoflavone and podocarpusflavone A. The structures of the compounds were established on the basis of NMR and MS data analysis. Besides, the content of biflavones of different specimens of C. pyramid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 12 publications
3
15
0
1
Order By: Relevance
“…The presence of gallic acid and ellagic acid was also evidenced in the flower extract in methanol . Other components identified were polyphenols (phenolic acid) in the fruit, and ursolic acid and quercetin from the bark of the stem and peel of the root (root and bark of the stem) thus confirming data from the literature (Bahia et al, 2010;Bahia et al, 2005).…”
Section: Flavanoids Of Agliconessupporting
confidence: 84%
See 1 more Smart Citation
“…The presence of gallic acid and ellagic acid was also evidenced in the flower extract in methanol . Other components identified were polyphenols (phenolic acid) in the fruit, and ursolic acid and quercetin from the bark of the stem and peel of the root (root and bark of the stem) thus confirming data from the literature (Bahia et al, 2010;Bahia et al, 2005).…”
Section: Flavanoids Of Agliconessupporting
confidence: 84%
“…A large number of metabolites have been isolated from `catingueira`, such as: phenylpropanoids, lupeol, β-sitosterol, bioflavonoids (agastiflavone, amentoflavone, sequoiaflavone and podocarpusflavone), chalcone, kaempferol, apigenin, lignane, stigamasterol and methyl gallate (Mendes et al, 2000;Bahia et al, 2010;Novais et al, 2003). Crude ethyl acetate from the leaves and roots of C. pyramidalis Tull.…”
Section: Introductionmentioning
confidence: 99%
“…L. P. Queiroz is an arboreal species belonging to the family Fabaceae, endemic to the northeastern region of Brazil, mainly in the caatinga biome, popularly known as "catingueira", "pau de porco", "catinga de porco", "pau de rato", "mussilaba" e "catingueira-das-folhas-largas" [1]. It is used in tradicional medicine for the treatment of gastritis, colic, diarrhea, asthma, bronchitis, diabetes, as an expectorant, cicatrizant, antiinflammatory and diuretic [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigations showed the presence of terpenes, lignans, tannins, flavonoids, and mainly bioflavonoids [9,10]. The kaempferol was isolated from the chloroformic extract of the leaves of P. pyramidalis, and several studies have demonstrated pharmacological potential of this compound, especially its anti-inflammatory properties [2,11].…”
Section: Introductionmentioning
confidence: 99%